A NUMERICAL STUDY OF JOULE HEATING EFFECT IN ELECTRODEPOSITION PROCESS-CASE OF COPPER ELECTRODEPOSITION - Hussein, Watheq; Mohammed Ali Alshuraifi; Bashar Abid Hamza; Raheem Aziz Hussein (Malaysian Journal of Science, 2023)
The electrochemical process in the presence of heat dissipation effect (Joule heating effect) is highly detected in practical electroplating solutions such as 0.6 M CuSO4+0.5 M H2SO4 electrolyte, where currents passing through the cathode-anode-electrolyte increase temperature in the electrolyte and electrodes. Due to the complex nature of such systems and the diversity of physics describing it, a theoretical approach of appearance for natural convection on vertical and horizontal sides of a cathode in the presence and absence of Joule effect under unsteady state condition was observed using Comsol Multiphysics. It was found that the onset of natural convection on a vertical side depends on the Joule effect, and the time (tn) for appearance is longer on the edges than in other areas. The horizontal side of a cathode assists the appearance of natural convection in the presence and absence of the Joule effect. The Rayleigh (Ra) number has larger values on the vertical side than the horizontal side due to the effect of surface concentration distribution Cs. A Sherwood, Sh-Ra mathematical relation such that Sh=0.03Ra0.86 was proposed where natural convection had no pronounced effect on the deposition process. It was found that the Joule heating effect negatively affects the electrodeposition process by reducing the local current values.